1981
DOI: 10.1111/j.1365-2885.1981.tb00718.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic studies of theophylline in dogs

Abstract: The pharmacokinetics of theophylline were investigated in dogs following intravenous, single oral, and multiple oral doses of aminophylline. Mean half-life (t1/2) of theophylline following single intravenous administration was 5.7 h and the apparent specific volume of distribution (V'd area) was 0.82 litre/kg. The bioavailability of theophylline was high (91%) following oral administration of aminophylline tablets and the absorption half-life (t1/2ab) was 0.4 h. Theophylline plasma concentrations observed foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…16 Although the pharmacokinetics of theophylline in the dog are well established, 17 only anecdotal reports address the occasional effectiveness of this drug for dogs with chronic bronchitis. 16 Although the pharmacokinetics of theophylline in the dog are well established, 17 only anecdotal reports address the occasional effectiveness of this drug for dogs with chronic bronchitis.…”
Section: Management and Monitoringmentioning
confidence: 99%
“…16 Although the pharmacokinetics of theophylline in the dog are well established, 17 only anecdotal reports address the occasional effectiveness of this drug for dogs with chronic bronchitis. 16 Although the pharmacokinetics of theophylline in the dog are well established, 17 only anecdotal reports address the occasional effectiveness of this drug for dogs with chronic bronchitis.…”
Section: Management and Monitoringmentioning
confidence: 99%
“…Two oral formulations of theophylline exist: rapid release and extended release; specific products of both have been previously evaluated in dogs. Prior studies have shown excellent oral bioavailability of theophylline (>91%) (McKiernan, Neff‐Davis, Koritz, Davis, & Pheris, ; Tse & Szeto, ) as well as low plasma protein binding (Munsiff, Koritz, McKiernan, & Neff‐Davis, ). Evaluation of an oral, rapid release formulation of aminophylline (the ethylenediamine salt of theophylline) demonstrated a short half‐life.…”
Section: Introductionmentioning
confidence: 99%
“…Errecalde et al, 1984;Ingvast Larson et al, 1985McKiernan et aL, 1981McKiernan et al, 1983Rail, 1980Davis et al, 1987Koritz et aL, 1981 A longer half-life is one of the goals in designing a slow-release formulation. This has not been accomplished in this case.…”
Section: Discussionmentioning
confidence: 98%
“…It has also been indicated as a treatment for respiratory conditions in domestic animals (Davis, 1980;McKiernan et al, 1981;Koritz et al, 1986). This drug is a methylxanthine derivative, a phosphodiesterase inhibitor (Ziment, 1978), and has been used in horses suffering from chronic obstructive pulmonary disease (COPD) (Beech, 1979;Thomson and McPherson, 1983).…”
Section: Introductionmentioning
confidence: 98%